Nietzsche e o direito - Fernandes, Rodrigo Rosas (2005)
Friedrich Wilhelm Nietzsche is still practically unknown among those who study the philosophy of law. Nietzsche studied several topics related to the science and to the philosophy of law, approaching juridical questions from a philosophic point of view and approaching philosophic questions from a juridical point of view, making several concepts transferations which goal is to make a critic of the law in modernity, a critic of the moral values that come from it, and also to propose an ethic that characterizes itself by a transvaloration of the western values. The genealogy of the primitive law in contrast with the paradigms of modern law, confirms both Nietzsche´s critics and ethic proposals. Having the law and the relations between Nietzsche and the free-thinker David Friedrich Strauss (1808-1874) as conductors, the purpose of the present work is to find a philosophy of law in Nietzsche s thinking and to bring more visibility for that segment of Nietzsche s thought